«Exemplares novelas» e «novelas exemplares» : Os paratextos da ficção em prosa no século XVII - Nemésio, Maria Inês (2018)
Selecting as corpus a group of fictional prose narratives of considerable length, published in the 17th century, this paper, entitled ‘«Exemplary novels» and exemplary novels: the paratexts of fiction during the 17th century’ aims to study the group of paratexts which accompany these works, paying special attention to censorship and dedications, and also to prologues, so as to identify networks of «cliental» relationships which may contribute to aiding the understanding of the circulation and «readings» in the sixteen-hundreds. Studying the paratexts, in relation to the texts, allows for the detection of ways in which fictional prose was legitimised, many times in an adverse context, with regard to censorial mechanisms, also contributing to the study of the censorial institution in the 17th century in Portugal.